2016
DOI: 10.1177/2168479016662902
|View full text |Cite
|
Sign up to set email alerts
|

Patient Engagement at a Tipping Point—The Need for Cultural Change Across Patient, Sponsor, and Regulator Stakeholders: Insights From the DIA Conference, “Patient Engagement in Benefit Risk Assessment Throughout the Life Cycle of Medical Products”

Abstract: Benefit-risk assessment is the foundation for decision making throughout the life cycle of medical products. Because patients are the beneficiaries of the efficacy of medical treatments and also bear their possible risks, their perspectives and judgments about value and the relative importance of benefits and risks should be at the heart of the medical decision-making process. Patient engagement is now at a tipping point; there have been a growing number of patient engagement initiatives over the past several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 13 publications
0
33
0
Order By: Relevance
“…PE in the research and development setting especially has received much focus with the development of frameworks or guidance . There are also guidance or frameworks at other milestones such as in health technology appraisal, benefit‐risk assessment and in value determination . The issue of definition and terminology of PE and patient centricity has also highlighted the need for a common understanding to facilitate multistakeholder teamwork .…”
Section: Introductionmentioning
confidence: 99%
“…PE in the research and development setting especially has received much focus with the development of frameworks or guidance . There are also guidance or frameworks at other milestones such as in health technology appraisal, benefit‐risk assessment and in value determination . The issue of definition and terminology of PE and patient centricity has also highlighted the need for a common understanding to facilitate multistakeholder teamwork .…”
Section: Introductionmentioning
confidence: 99%
“…Consumer involvement provides a direct opportunity in this context to help researchers, clinicians, and multi-stakeholder groups resolve uncertainties about the design of pandemic research and the appropriateness of the risk-benefit balance proposed (Smith et al, 2016 ). For example, a common contentious issue is the use of health data, yet the need for data to understand and address the pandemic is unprecedented.…”
Section: Consumer Involvement In Pandemic Research: Challenges and Opmentioning
confidence: 99%
“…eConsent was mentioned as the top planned initiative (11 companies). Other planned initiatives mentioned by less than half of the group (10 companies) were adaptive trial designs and adaptive licensing; patient communities during and after clinical trials were also reported to be a planned initiative (11). Medicine co-development partnerships were reported by many companies as not being considered.…”
Section: Innovative Partnershipsmentioning
confidence: 99%
“…There are a number of challenges with the use of mobile health applications, including data security and privacy, data qualification, and validation and regulatory acceptance. 10 Smith et al 11 discussed the need for a common language, alignment, and best practices around patient engagement. The Patient-Centered Outcomes Research Institute (Washington, DC) has developed general guidance through their Engagement Rubric, which describes how input from patients and other stakeholders can be gathered throughout the research cycle.…”
Section: Introductionmentioning
confidence: 99%